National transportation planning model for the Philippines a framework for development - Reyes, Valentin A.
This paper intends to lay the groundwork for the development of a national transportation planning model for the country. The framework is essentially that of a simulation model designed with the use of the systems approach. Basically, it considers two types of movement, namely those of passengers and commodities, on the major modes of transport in the country, that is, land, water and air. Passenger travel is modelled on an intraregional as well as interregional basis. For the intraregional trips, which are termed as local travel by the study, passenger movement is correlated with the demographic and socio-economic characteristics are taken to be indicative of land use potentials. On the other hand, the treatment of long-distance or interregional passenger travel is more straightforward, making use of growth factors and general variables such as income per capita and population growth. Commodity flows, which include services transported, are drawn from regional supply and demand figures by industry. The latter are disaggregated into major subcommodity groups and are allocated from surplus to deficit areas through linear programming and statistically-based gravity methods. This portion of the model assumes the availability of inputs from an exogenous macroeconomic model using input-output analysis at the regional level. Due to the vast data requisites of the model, the use of the computer as one of the analytical tools in the study is a must.